PENINGKATAN KAPASITAS KELOMPOK TANI DALAM MENGOLAH PAKAN IKAN ALTERNATIF BERBASIS LIMBAH ORGANIK - Yuli Andriani; Muhamad Fatah Wiyatna; Fittrie Meyllianawaty Pratiw; Rusky Intan Pratama (Jurnal Abdi Insani, 2023)
Most of the waste generated by residents in Sumedang area is in the form of organic waste. The abundance of household waste such as rice, vegetable waste, animal waste can be utilized by the community as a solution to the household waste accumulation. The potential for organic waste from domestic activities is one source that can be applied as fish feed. The purpose of this activity is therefore that the community can utilize the potential of household waste originate around their area as a raw material for fish feed. The method applied in this activity was counseling containing information and demonstrations on the utilization of organic waste into fish feed with fermentation techniques provided by resource persons from academics. The target audience for this activity is the community in the location, namely Gudang Village, Tanjungsari District, Sumedang Regency, especially the Freshwater Fisheries Group. The parties that support the implementation of this activity include the Biomethagreen Education House and community members in the location. Counseling on the manufacture of fish feed is very beneficial for people who have daily agricultural and fish and poultry farming activities in the hope of being able to reduce the amount of waste that pollutes the environment and utilize household waste as feed. The good response and enthusiasm given by the participants at the location was a factor that contributed to the smooth running of this activity. The Gudang Village community, which has high potential in carrying out fishery and livestock activities, makes it an opportunity to provide feed sourced from household waste raw materials, not only for fish feed but can also be used for animal feed.